The Effects of Policy Expectations on Crop Supply, with an Application to Base Updating. (2nd January 2014) - Hendricks, Nathan P.; Sumner, Daniel A.
Abstract: We develop a dynamic model to assess the effects of policy expectations on crop supply and illustrate the approach with estimates of the effects of base updating in U.S. crop programs. For corn and soybeans in the Corn Belt, the effect of base updating is relatively small because relevant crop alternatives are subject to similar policies and the alternatives are substitutes in production. Increasing acreage of one program crop to capture future payments from base updating reduces future payments from the alternative crop. We also use our model to assess the effect of base updating on acreage response to prices.